Co-occurrence of mosquito larvae in stagnant water in residential areas in Malaysia - Low, V.L.; Chen, C.D.; Lee, H.L.; Lim, P.E.; Leong, C.S.; Sofian-Azirun, Mohd (2013)
Background: The importance of mosquito-borne diseases can be aggravated when there is an occurrence of mixed infestation between the mosquitoes in a habitat. However, there is limited available information on mixed infestation behavior among Malaysian mosquitoes. Objective: We elucidated the nature of co-occurrence among mosquito species from residential areas in Malaysia. Methods: Entomological investigation was carried out by using a previously described larval dipping method in 20 residential areas across 11 states and a federal territory (i.e., Kuala Lumpur) in Peninsular Malaysia as well as two states in East Malaysia. Results: Of 20 study sites, eight study sites exhibited co-occurrence of mosquito larvae, ranging from 1.28 to 50.00. Culex quinquefasciatus was able to breed simultaneously with Cx. gelidus (10.00-50.00), Lutzia fuscanus (2.94-13.33), Cx. vishnui (5.00) and Armigeres subalbatus (1.28-3.77). On the other hand, Cx. vishnui was able to breed simultaneously with Cx. gelidus (20.00) and Lu. fuscanus (3.33). Conclusion: The findings of this study have implications for the development of a better understanding of their mixed infestation behavior and prevention of vector-borne disease transmission from these study sites.